Constructing knowledge in primary physical education: a critical perspective from pre-service teachers. Issue 1 (2nd January 2021) - Randall, Vicky; Fleet, Matthew
ABSTRACT: Primary physical education is quickly becoming an area of academic interest with a particular focus on new entrants into the profession. This study adopts a Personal Construct methodology to identify how pre-service teachers in England construct their knowledge of primary physical education. Our findings present four themes for knowledge development, taken from four repertory grid interviews: knowledge perspectives, knowledge validation, knowledge context and knowledge application. Participants expressed they had limited provision for physical education when on a school-based placement, which was attributed to subject outsourcing and a lack of teacher and mentor confidence. The study highlights the importance of professional socialisation through initial teacher education programmes, with opportunities for pre-service teachers to engage with 'knowledgeable others'. In the absence of opportunity for primary pre-service teachers to develop knowledge in physical education, we caution it is unlikely the issue of teacher competence will improve.